ANALISIS BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSETS(ROA) - Kurniasari, Rani (www.bsi.ac.id, 2017)
Banking in Indonesia is progressing rapidly every day. Sophisticated banking transactions make it easier for individuals or companies to use banking services. Related to these conditions will certainly increase the number of transactions in the Bank including at PT. State Savings Bank. To support banking activities, PT. Bank Tabungan Negara always wants to be a healthy bank with a high level of performance efficiency and gain a significant advantage. In the correlation coefficient test results at Bank Tabungan Negara can be seen that the relationship between Operational Costs and Operating Income (BOPO) to Return On Assets (ROA) is having a weak and unidirectional relationship. From the result of determination coefficient of determination of Return On Assets (ROA) influenced by Operational Cost and Operating Income (BOPO) equal to 47,7% the rest 52,3% influenced by other factor. The calculation results show the regression equation Y = 4.793 - 0.039x formed can be seen that the constant of 4.793 states that if there is no Operational Cost and Operating Income (ROA) thenReturn On Assets (ROA) will be 4.793%. With the regression coefficient x of -0.039. Stated that if Operational Cost and Operating Income (BOPO) increased one unit (1%) will reduce Return On Assets (ROA) by 0,039%. Keywords: BOPO, ROA